Intracellular delivery of oligonucleotides in Helicobacter pylori by fusogenic liposomes in the presence of gastric mucus. (September 2017) - Santos, Rita S.; Dakwar, George R.; Zagato, Elisa; Brans, Toon; Figueiredo, Céu; Raemdonck, Koen; Azevedo, Nuno F.; De Smedt, Stefaan C.; Braeckmans, Kevin
Abstract: The rising antimicrobial resistance contributes to 25000 annual deaths in Europe. This threat to the public health can only be tackled if novel antimicrobials are developed, combined with a more precise use of the currently available antibiotics through the implementation of fast, specific, diagnostic methods. Nucleic acid mimics (NAMs) that are able to hybridize intracellular bacterial RNA have the potential to become such a new class of antimicrobials and additionally could serve as specific detection probes. However, an essential requirement is that these NAMs should be delivered into the bacterial cytoplasm, which is a particular challenge given the fact that they are charged macromolecules. We consider these delivery challenges in relation to the gastric pathogen Helicobacter pylori, the most frequent chronic infection worldwide. In particular, we evaluate if cationic fusogenic liposomes are suitable carriers to deliver NAMs across the gastric mucus barrier and the bacterial envelope. Our study shows that DOTAP-DOPE liposomes post-PEGylated with DSPE-PEG (DSPE Lpx) can indeed successfully deliver NAMs into Helicobacter pylori, while offering protection to the NAMs from binding and inactivation in gastric mucus isolated from pigs. DSPE Lpx thus offer exciting new possibilities for in vivo diagnosis and treatment of Helicobacter pylori infections.